Reviving The Forgotten Component Environmental Education In Mainstream Pedagogy - Martha Betaubun; Arin Mantara Anggawirya; Desy Eva Laila Rokhmah (Technium Social Sciences Journal, 2023)
This paper presents the results of an analysis of the implementation of Environmental Education at the formal and higher education levels. EE is often overlooked in learning, yet it is crucial to ensuring human survival. This research was conducted by revisiting the main goals of EE in the classroom, by building a framework of interconnections using the Theory of Change (ToC) between classroom interactions and their impact on improving insight and knowledge at formal education and higher education levels. The results of this research indicate that (1) The implementation of EE is still predominantly in the Cognitive Domain (2) learning interaction implementation has not yet had a significant impact on the practical elements expected from EE (3) Formal education contributes more than higher education in the context of EE.